Pro-Inflammatory Cytokines in Patients With Chronic Phase-Chronic Myeloid Leukaemia Treated With Imatinib: Any Role in the Monitoring of Treatment Response? - Kehinde A. Taiwo; Ibrahim O. Ahmed; Muritala A. Asafa; Olusola J. Olarewaju; Oludolapo A. Omoyiola; Olatokunbo O. Oguns; Temilola O. Owojuyigbe; Rahman A. Bolarinwa (Biomarker Insights)
Background: Cancers cause changes in the levels of inflammatory cytokines by inhibiting or promoting their production thus affecting the immune system. The measurement of serum levels of cytokines may be useful in assessing these immunological changes and invariably assessing cancer status. Objectives: To investigate the effect of imatinib mesylate (glivec ® ) on the serum levels of interleukins (IL-6 and IL-10), and C-reactive protein (CRP) in patients with chronic phase chronic myeloid leukaemia (CP-CML). Design: This prospective cohort study included 26 imatinib naïve CP-CML patients with no other co-morbidities and 26 age and sex-matched healthy controls. Method: Serum levels of interleukins (IL6 and 10) and CRP were determined using the ELISA method at recruitment for both patients and controls and repeated for the CML patients at 3 months into imatinib therapy. Results: The mean serum levels of IL-6 and CRP were significantly higher in CP-CML than in the controls at recruitment 439.83 ± 167.52 versus 39.62 ± 10.11 pg/ml, ( t  = 8.720 P  ⩽ .0001), (8.45 ± 2.88 vs 2.86 ± 1.08 mg/l; t  = 6.729 P  ⩽ .0001) respectively. In contrast, the mean of the IL-10 in the controls (36.63 ± 12.43) was noticed to be significantly higher than the patients (22.88 ± 4.76 vs 36.63 ± 12.43 pg/ml; t  = −3.851 P  = .003). Interestingly, there was a significant drop in the serum levels of IL-6 (439.83 ± 167.52 vs 46.85 ± 14.48 pg/ml, ( t  = 8.055 P  ⩽ .0001) and CRP (8.45 ± 2.88 mg/l vs 4.24 ± 1.57; t  = 4.305 P  = .0001) in the CML subjects 3 months into imatinib therapy. Only IL-10 had a non-significant drop in the CML subjects after 3 months of imatinib therapy. Method validation of these biomarkers was done using the Receiver operating characteristic (ROC) curve which revealed an area under the curve (AUC) of 1.000 for both IL-6 and CRP and 0.152 for IL-10. Conclusion: The study has concluded that treatment naïve CML is associated with a significant elevation of pro-inflammatory cytokines (IL-6 and CRP) and treatment with imatinib led to a significant decline in the serum levels of these markers suggesting that IL-6 and CRP could be useful as adjunct in the monitoring of CML treatment.